Contributory Factors to Malnutrition in Children under Five Years Received in Consultation at the Pediatric Service of Saint Martin of Papane Hospital in Northeast Benin - Gbessohele Justin, Behanzin; Bouko Boni Orou Marius, Bio; Christophe, Chabi; Diloua, Bayangbe; Ange, Okouidjo; Abdou Ganiou, Yessoufou (Journal of Pediatric Health And Nutrition, 2026)
Malnutrition is a major global public health issue, especially in low-income regions. Identifying contributing factors is crucial for effective interventions. This study aims to determine the factors contributing to malnutrition among children under 5 years old at Papané Hospital in northeast Benin from April 6 to July 6, 2021. A descriptive and analytical study was conducted, involving structured questionnaires administered to 208 children aged 0 to 59 months and their parents or guardians. The study focused on socioeconomic characteristics and feeding practices. Predominantly male children (sex ratio 1.2) and mostly uneducated homemaker mothers were involved. Data were processed using Excel, WHO Anthro, and SPSS software. Statistical significance was assessed with SPSS, using a margin of error of 0.05. Results showed that 74.88% of the children experienced stunted growth, 90.34% suffered from wasting, and 79.43% were underweight. Exclusive breastfeeding was significantly linked to lower rates of severe malnutrition (p = 0.0075). Gradual weaning was associated with better nutritional outcomes compared to abrupt weaning (p = 0.000). Higher malnutrition rates were found among children of single mothers (36.06%) and those from polygamous households (49.52%). Maternal education level did not significantly affect children's nutritional status (p = 0.53). Breastfeeding practices and household dynamics are essential for improving the nutritional status of children under five. A multidimensional approach is needed to address the complex factors contributing to malnutrition.
Keywords: Malnutrition; children under five; breastfeeding; weaning practices; household dynamics; Papané Hospital; Benin